Identifying Behavioral Responses to Tax Reforms: New Insights and a New Approach - Katrine M. Jakobsen; Jakob Egholt Søgaard (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
We revisit the identification of behavioral responses to tax reforms and develop a new approach that allows for graphical validation of identifying assumptions and representation of treatment effects. Considering typical tax reforms, such as a reduction in the top income tax, we show that the state-of-the-art estimation strategy relies on an assumption that trend differences in income across the income distribution remain constant in the absence of reforms. Similar to the pre-trend validation of differencesin-differences studies, this identifying assumption of constant trend differentials can be validated by comparing the evolution of income in untreated parts of the income distribution over time. We illustrate the importance of our new validation approach by studying a number of tax reforms in Denmark, and we show how violations of the identifying assumption may drive the estimates obtained from the state-of-the-art strategy.
Keywords: C14; H30; J22; 330; Tax Reforms; Behavioral Responses; Identification; Validation